A radial standing Pc5-6 wave and its energy coupling with field line resonance within the dusk-sector magnetosphere - Zhou,Y-J; He,F; Zhang,X-X; Archer,MO; Lin,Y; Ma,H; Tian,A-M; Yao,Z-H; Wei,Y; Ni,B; Liu,W; Zong,Q-G; et al. (JGR: Space Physics, 2023)
Global ultra-low frequency (ULF) oscillations are believed to play a significant role in the mass, energy, and momentum transport within the Earth's magnetosphere. In this letter, we observe a ∼1.2 mHz radial standing wave in the dusk-sector magnetosphere accompanied by the field line resonance (FLR) on 16 July 2017. The frequency estimation from the simple box model also confirms the radial standing wave. The essential characteristics of FLR are concurrently identified at the dusk-sector magnetosphere and the conjugated ground location. Further, the radial standing wave dissipates energy into upper atmosphere to enhance the local aurora by coupling itself to the FLR. The magnetospheric dominant 1.2/1.1 mHz ULF waves plausibly correspond well with the discrete ∼1 mHz magnetosheath ion dynamic pressure/velocity oscillation, suggesting this radial standing wave and FLR in the flank magnetosphere may be triggered by the solar-wind and/or magnetosheath dynamic pressure/velocity fluctuations.